A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE): JWST supports earlier reionization around (O III) emitters - Jin, Xiangyu; Yang, Jinyi; Fan, Xiaohui; Wang, Feige; Kakiichi, Koki; Meyer, Romain A.; Becker, George D.; Zou, Siwei; Bañados, Eduardo; Champagne, Jaclyn B.; D’Odorico, Valentina; Yue, Minghao; et al. (The astrophysical journal, 2024)
Understanding when and how reionization happened is crucial for studying the early structure formation and the properties of the first galaxies in the Universe. At z > 5.5, the observed intergalactic medium (IGM) optical depth shows a significant scatter, indicating an inhomogeneous reionization process. However, the nature of the inhomogeneous reionization remains debated. A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE) is a JWST Cycle 1 program that has spectroscopically identified >400 [O iii] emitters in 25 quasar fields at z > 6.5. Combined with deep ground-based optical spectroscopy of ASPIRE quasars, the ASPIRE program provides the current largest sample for IGM-galaxy connection studies during cosmic reionization. We present the first results of IGM effective optical depth measurements around [O iii] emitters using 14 ASPIRE quasar fields. We find the IGM transmission is tightly related to reionization era galaxies to the extent that a significant excess of Lyα transmission exists around [O iii] emitters. We measure the stacked IGM effective optical depth of IGM patches associated with [O iii] emitters and find they reach the same IGM effective optical depth at least d z ∼ 0.1 ahead of those IGM patches where no [O iii] emitters are detected, supporting earlier reionization around [O iii] emitters. Our results indicate an enhancement in IGM Lyα transmission around [O iii] emitters at scales beyond 25 h −1 cMpc, consistent with the predicted topology of reionization from fluctuating UV background models.
Im Zusatz zum Titel steht "O III" in eckigen Klammern
Online verfügbar: 14. November 2024
Gesehen am 03.06.2025